EXPLORING PHRASEOLOGICAL UNITS IN ENGLISH TONGUE TWISTERS: A LINGUISTIC PERSPECTIVE - Sevarakhon Dekhkonova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article delves into the role of phraseological units within English tongue twisters, examining how these linguistic constructs contribute to their unique phonetic and semantic properties. Tongue twisters are playful and challenging phrases designed to test and develop pronunciation skills. By analyzing their phraseological components, we gain insights into how fixed expressions, idiomatic language, and syntactic patterns are employed to create engaging and memorable linguistic puzzles. This exploration highlights the interplay between language structure, phonetic complexity, and cognitive processing in tongue twisters.